2020
DOI: 10.4314/sajas.v49i6.9
|View full text |Cite
|
Sign up to set email alerts
|

Response of growing chicks to supplementation of low protein diets with leucine, valine and glycine-glutamic acid

Abstract: This experiment was conducted to determine the interaction effects that resulted from supplementation of low-protein diets with leucine (Leu), valine (Val), and glycine-glutamic acid (Gly-Glu) on growing broiler chicks from 11 to 24 days old. Two levels of digestible Leu (1.07 and 1.50%) and three levels of digestible Val (0.64, 0.74, and 0.84%) were investigated as a 2 × 3 factorial arrangement of treatments with 12 replicates. The diet with 1.07% digestible Leu and 0.84% digestible Val was supplemented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…In the present study, dietary leucine and HMB had beneficial effects on broiler performance during the finisher phase. These effects may be attributed to an appropriate ratio among BCAA of the finisher diet used and reduced valine and isoleucine requirements 8,33 . This may explain why the dietary leucine could have compromised broiler performance in our study 5,9,10 .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In the present study, dietary leucine and HMB had beneficial effects on broiler performance during the finisher phase. These effects may be attributed to an appropriate ratio among BCAA of the finisher diet used and reduced valine and isoleucine requirements 8,33 . This may explain why the dietary leucine could have compromised broiler performance in our study 5,9,10 .…”
Section: Discussionmentioning
confidence: 81%
“…These effects may be attributed to an appropriate ratio among BCAA of the finisher diet used and reduced valine and isoleucine requirements. 8,33 This may explain why the dietary leucine could have compromised broiler performance in our study. 5,9,10 Also, during the starter phase, the decrease in the FI of the LLPD broilers could have induced a deficiency of isoleucine and valine as well, which is associated with growth depression.…”
Section: Discussionmentioning
confidence: 82%
“…These amino acids are catabolized in intestinal cells and are important for intestinal nutrient absorption. Therefore, any changes in intestinal morphometric structure may affect nutrient metabolizability and performance (Adabi et al, 2019), and duodenum weight may be important in facilitating BWG in young broilers (Wijtten et al, 2010). The digestible valine levels increased villus height and V:C ratio in the jejunum only in the broilers from 52-week-old breeders, indicating that breeder age affects intestinal development in broilers in response to the diet.…”
Section: Discussionmentioning
confidence: 99%
“…The digestible valine levels increased villus height and V:C ratio in the jejunum only in the broilers from 52-week-old breeders, indicating that breeder age affects intestinal development in broilers in response to the diet. According to Adabi et al (2019), the observed improvement in the jejunum with the increasing valine levels may be attributed to the utilization of dietary valine as a precursor of nonessential amino acids in the mucosa. Branched-chain amino acids could enhance intestinal development by increasing the local glucose uptake for animals and humans, since they regulate the expression and translocation of intestinal glucose transporters through insulin-dependent or insulin-independent pathways (Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous experiments and initiatives have aimed to diminish the reliance on animal protein in broiler chicken diets since the onset of the new millennium. However, some endeavors have fallen short of achieving satisfactory performance outcomes compared to conventional animal protein diets, The primary factors contributing to the suboptimal growth performance of broiler chickens can be attributed to deficiencies in non-essential amino acids and the competition among branched-chain amino acids (BCAA) [4]. Although there has been a noteworthy shift from employing Total Amino Acids (TAA) to Digestible Amino Acids (DAA) when designing poultry diets, some entities or nutritionists still formulate broiler diets based on TAA requirements.…”
Section: Introductionmentioning
confidence: 99%